Molecular sieve SSZ-120, its synthesis and use
By synthesizing a reaction mixture containing a specific structural guide agent, the problem of difficult to synthesize aluminum germanium silicate molecular sieve with small crystal size and high surface area in the prior art is solved, and the efficient synthesis and efficient catalytic effect of SSZ-120 molecular sieve is achieved.
Patent Information
- Application Number
- CN202180039980.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-05-22
- Filing Date
- 2021-05-18
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2041-05-18
AI Technical Summary
It is difficult to synthesize aluminum germanium silicate molecular sieves with small crystal size and high surface area in the prior art, and there is a lack of efficient catalysts during the conversion and adsorption of organic compounds.
SSZ-120 molecular sieve was synthesized by providing a reaction mixture containing FAU skeleton type zeolite, germanium source, structural guide 3,3'-[2,6-naphthalene bis(methylene)]bis[1,2-dimethyl-1H-imidazole] biscation, fluoride ion and water and subjecting them to crystallization conditions sufficient to form aluminogermanium silicate molecular sieve crystals. The molecular sieve has specific powder X-ray diffraction spectrograms and high surface area characteristics in its initial synthetic and calcined form.
The efficient synthesis of aluminum germanium silicate molecular sieve SSZ-120 has a small crystal size and a high surface area. It is suitable for catalysts in organic compound conversion reaction and adsorption process, significantly improving catalytic efficiency and selectivity.
Smart Images

Figure CN115697909B_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to and the benefit of U.S. Provisional Application Serial No. 63 / 028,642, filed on May 22, 2020. Technical Field
[0003] The present disclosure relates to a small crystal size, high surface area aluminum germanosilicate molecular sieve designated SSZ-120, its synthesis and its use in organic compound conversion reactions and adsorption processes. Background Art
[0004] Molecular sieves are a class of commercially important materials that have different crystal structures and defined pore structures, as indicated by different X-ray diffraction (XRD) patterns, and specific chemical compositions. The crystal structure defines cavities and pores that are characteristic of a particular type of molecular sieve.
[0005] According to the present disclosure, a small crystal size, high surface area aluminum germanosilicate molecular sieve named SSZ-120 and having a unique powder X-ray diffraction pattern has been synthesized using 3,3'-[2,6-naphthalenebis(methylene)]bis[1,2-dimethyl-1H-imidazole] dianion as a structure directing agent. Summary of the invention
[0006] In a first aspect, an aluminum germanosilicate molecular sieve is provided, which in its calcined form has a powder X-ray diffraction spectrum comprising the peaks in the following table:
[0007]
[0008]
[0009] The calcined molecular sieve may have a molecular weight of at least 500 m / s as determined by the t-plot method of nitrogen physical adsorption. 2 / g of total surface area, and / or at least 100 m2 as determined by the t-curve method of nitrogen physical adsorption 2 / g of external surface area.
[0010] In a second aspect, there is provided an aluminum germanosilicate molecular sieve having, in its as-synthesized form, a powder X-ray diffraction pattern comprising the peaks in the following table:
[0011]
[0012] In its as-synthesized and anhydrous form, the aluminogermanosilicate molecular sieve may have a chemical composition including the following molar relationship:
[0013] Widest secondary <![CDATA[(SiO 2 +GeO 2 ) / To 2 OR 3 ]]> ≥30 ≥60 <![CDATA[Q / (SiO 2 +GeO 2 )]]> >0 to 0.1 >0 to 0.1
[0014] wherein Q comprises a 3,3'-[2,6-naphthalenebis(methylene)]bis[1,2-dimethyl-1H-imidazolium] dication.
[0015] In a third aspect, a method for synthesizing an aluminum germanosilicate molecular sieve is provided, the method comprising (1) providing a reaction mixture comprising (a) a FAU framework-type zeolite; (b) a germanium source; (c) a structure directing agent (Q) comprising a 3,3'-[2,6-naphthalenebis(methylene)]bis[1,2-dimethyl-1H-imidazolium] dication; (d) a fluoride ion source; and (e) water; and (2) subjecting the reaction mixture to crystallization conditions sufficient to form aluminum germanosilicate molecular sieve crystals.
[0016] In a fourth aspect, a process is provided for converting a feedstock comprising an organic compound to a conversion product, the process comprising contacting the feedstock under organic compound conversion conditions with a catalyst comprising an active form of an aluminogermanosilicate molecular sieve as described herein.
[0017] In a fifth aspect, there is provided an organic nitrogen compound comprising a dication having the structure:
[0018] BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The powder X-ray diffraction (XRD) spectrum of the initial synthesis product of Example 2 is shown.
[0021] Figure 2(A) to Figure 2(D) Scanning electron micrograph (SEM) images of the initial synthesis product of Example 2 at different magnifications are shown.
[0022] Figure 3 The powder XRD spectrum of the calcined product of Example 3 is shown.
[0023] Figure 4 is a graph illustrating the relationship between conversion or yield and temperature in the hydroconversion of n-decane over a Pd / SSZ-120 catalyst. DETAILED DESCRIPTION
[0024] definition
[0025] The term "framework type" has the meaning described in "Atlas of Zeolite Framework Types" by Ch. Baerlocher and LB McCusker and DH Olsen (6th revised edition, Elsevier, 2007).
[0026] The term "zeolite" refers to an aluminosilicate molecular sieve having a framework composed of aluminum oxide and silicon dioxide (ie, repeating AlO4 and SiO4 tetrahedral units).
[0027] The term "aluminum germanosilicate" refers to a molecular sieve having a framework consisting of AlO4, GeO4 and SiO4 tetrahedral units. Aluminum germanosilicate may contain only the named oxides, in which case it may be described as "pure aluminum germanosilicate" or it may contain other additional oxides.
[0028] The term "as-synthesized" is used herein to refer to the molecular sieve in its form after crystallization, but prior to removal of the structure directing agent.
[0029] The term "anhydrous" is used herein to refer to molecular sieves that are substantially free of physically adsorbed water and chemically adsorbed water.
[0030] The term "SiO 2 / Al 2 O 3 The molar ratio can be abbreviated as SAR.
[0031] Synthesis of molecular sieves
[0032] Aluminogermanosilicate molecular sieve SSZ-120 can be synthesized by: (1) providing a reaction mixture comprising (a) a FAU framework-type zeolite; (b) a germanium source; (c) a structure directing agent (Q) comprising a 3,3'-[2,6-naphthalenebis(methylene)]bis[1,2-dimethyl-1H-imidazole] dication; (d) a fluoride ion source; and (e) water; and (2) subjecting the reaction mixture to crystallization conditions sufficient to form aluminum-germanosilicate molecular sieve crystals.
[0033] The reaction mixture may have a composition expressed in molar ratios within the ranges listed in Table 1:
[0034] Table 1
[0035] Reactants Widest secondary <![CDATA[(SiO 2 +GeO 2 ) / To 2 OR 3 ]]> 30 to 600 60 to 500 <![CDATA[Q / (SiO 2 +GeO 2 )]]> 0.10 to 1.00 0.20 to 0.70 <![CDATA[F / (SiO 2 +GeO 2 )]]> 0.10 to 1.00 0.20 to 0.70 <![CDATA[H 2 O / (SiO 2 +GeO 2 )]]> 2 to 10 4 to 8
[0036] wherein Q comprises a 3,3'-[2,6-naphthalenebis(methylene)]bis[1,2-dimethyl-1H-imidazolium] dication.
[0037] In some aspects, the reaction mixture can have SiO in the range of 4 to 12 (e.g., 6 to 10). 2 / GeO 2 Molar ratio.
[0038] The FAU framework type zeolite can be an ammonium type zeolite or a hydrogen type zeolite (e.g., NH 4Preferably, the FAU framework type zeolite is zeolite Y. More preferably, the zeolite Y has a SiO2 content in the range of about 30 to about 500. 2 / Al 2 O 3 molar ratio. The FAU framework type zeolite may comprise two or more zeolites. Typically, the two or more zeolites have different SiO 2 / Al 2 O 3 The FAU framework type zeolite can also be the sole source of silica and aluminum for forming the aluminogermanosilicate molecular sieves.
[0039] Germanium sources include germanium oxide and germanium alkoxides (eg, germanium ethoxide).
[0040] Fluoride ion sources include hydrogen fluoride, ammonium fluoride and ammonium bifluoride.
[0041] SSZ-120 can be synthesized using a structure directing agent (Q) comprising a 3,3'-[2,6-naphthalenebis(methylene)]bis[1,2-dimethyl-1H-imidazolium] dication represented by the following structure (1):
[0042]
[0043] Suitable sources of Q are hydroxides, chlorides, bromides and / or other salts of diquaternary ammonium compounds.
[0044] The reaction mixture may contain seeds of molecular sieve material (such as SSZ-120 from a previous synthesis) in an amount of 0.01 to 10,000 ppm by weight of the reaction mixture (e.g., 100 to 5000 ppm by weight). Seeding helps to increase the selectivity of SSZ-120 and / or shorten the crystallization process.
[0045] Note that the reaction mixture components may be provided by more than one source. In addition, one source may provide two or more reaction components. The reaction mixture may be prepared in batches or continuously.
[0046] Crystallization and post-synthesis processing
[0047] Crystallization of the molecular sieve from the above reaction mixture can be carried out under static, tumbling or stirring conditions in a suitable reactor vessel (such as a polypropylene tank or a polytetrafluoroethylene-lined or stainless steel autoclave) placed in a convection oven maintained at a temperature of 100° C. to 200° C. for a time sufficient for crystallization to occur at the temperature used (e.g., 1 day to 14 days). The hydrothermal crystallization process is usually carried out under autogenous pressure.
[0048] Once the desired molecular sieve crystals are formed, the solid product can be separated from the reaction mixture by standard mechanical separation techniques such as filtration or centrifugation. The recovered crystals are washed with water and then dried for a few seconds to a few minutes (e.g., 5 seconds to 10 minutes for rapid drying) or a few hours (e.g., 4 to 24 hours for oven drying at 75° C. to 150° C.) to obtain as-synthesized SSZ-120 crystals having at least a portion of the structure directing agent in their pores. The drying step can be carried out at atmospheric pressure or under vacuum.
[0049] The initially synthesized molecular sieve may also be subjected to heat treatment, ozone treatment or other treatment to remove some or all of the structure directing agents used in its synthesis. The removal of the structure directing agent may be carried out by heat treatment (i.e., calcination), wherein the initially synthesized molecular sieve is heated in air or an inert gas at a temperature sufficient to remove some or all of the structure directing agent. Although pressures below atmospheric pressure may be used for heat treatment, atmospheric pressure is required for convenience reasons. The heat treatment may be carried out at a temperature of at least 370°C for at least one minute and generally not longer than 20 hours (e.g., 1 to 12 hours). The heat treatment may be carried out at a temperature of up to 925°C. For example, the heat treatment may be carried out in air at a temperature of 400°C to 600°C for approximately 1 to 8 hours. The heat-treated product, especially its metal, hydrogen and ammonium forms, is particularly useful for the catalysis of certain organic (e.g., hydrocarbon) conversion reactions.
[0050] Any extra-framework metal cations in the molecular sieve may be replaced with hydrogen, ammonium, or any desired metal cation according to techniques well known in the art (eg, by ion exchange).
[0051] Characterization of Molecular Sieve
[0052] Molecular sieve SSZ-120 in its as-synthesized and anhydrous form may have a chemical composition including the following molar relationships listed in Table 2:
[0053] Table 2
[0054] Widest secondary <![CDATA[(SiO 2 +GeO 2 ) / To 2 OR 3 ]]> ≥30 ≥60 <![CDATA[Q / (SiO 2 +GeO 2 )]]> >0 to 0.1 >0 to 0.1
[0055] wherein Q comprises a 3,3'-[2,6-naphthalenebis(methylene)]bis[1,2-dimethyl-1H-imidazolium] dication.
[0056] In some aspects, the molecular sieve may have a SiO in the range of 4 to 12 (e.g., 6 to 10). 2 / GeO 2 Molar ratio.
[0057] Molecular sieve SSZ-120 in its calcined form may have a chemical composition comprising the following molar relationship:
[0058] Al 2 O 3 :(n)(SiO 2 +GeO 2 )
[0059] wherein n≥30 (eg, 30 to 600, ≥60, 60 to 500, or 100 to 300).
[0060] Molecular sieve SSZ-120 has a powder X-ray diffraction pattern including at least the peaks listed in Table 3 below in its as-synthesized form and at least the peaks listed in Table 4 in its calcined form.
[0061] Table 3 Characteristic peaks of the initially synthesized SSZ-120
[0062]
[0063] Table 4 Characteristic peaks of calcined SSZ-120
[0064]
[0065] The powder X-ray diffraction spectra provided herein are collected by standard techniques using copper K-α radiation. As will be appreciated by those skilled in the art, the determination of the parameter 2-θ is subject to the influence of human and mechanical errors, and the combination of human and mechanical errors can impose an uncertainty of about ± 0.3 ° on each reported 2-θ value. Of course, this uncertainty is also reflected in the reported d spacing values, which are calculated from the 2-θ values using Bragg's law. The relative intensity of the spectral line (I / Io) represents the ratio of the peak intensity to the intensity of the strongest spectral line above the background. The intensity is not corrected for the Lorentz effect and the polarization effect. The relative intensity is represented by the following symbols: VS = very strong (> 60 to 100), S = strong (> 40 to 60), M = medium (> 20 to 40), and W = weak (> 0 to 20).
[0066] Small changes in the powder X-ray diffraction spectrum (e.g., experimental changes in peak ratios and peak positions) may be caused by changes in the atomic ratios of the framework atoms due to changes in the lattice constant. In addition, sufficiently small crystals may affect the shape and intensity of the peaks, which may lead to peak broadening. Calcination can also cause small shifts in the powder X-ray diffraction spectrum compared to the powder X-ray diffraction spectrum before calcination. Despite these small perturbations, the lattice structure can remain unchanged after calcination.
[0067] The syntheses described herein can produce molecular sieves having small crystal sizes such that the total surface area of the material can be at least 500 m 2 / g and the outer surface area may be at least 100m 2 / g. In some aspects, the molecular sieve described herein may comprise a total external surface area of at least 600m 2 / g, at least 625m 2 / g, at least or at least 650m 2 / g, such as 500 to 800 m 2 / g, 600 to 800m 2 / g, or 650 to 800 m 2 Additionally or alternatively, the molecular sieve described herein may comprise an outer surface area of at least 100 m 2 / g, at least 110m 2 / g, at least 120m 2 / g, at least 130m 2 / g, or at least 140m 2 / g, such as 100 to 300 m 2 / g, 120 to 300m 2 / g, or 140 to 300m 2 / g of crystals. All surface area values given herein were determined from nitrogen physical adsorption using the t-curve method. Details of this method are described by BC Lippens and JH de Boer (J. Catal. 1965, 4, 319-323).
[0068] Industrial Applicability
[0069] Molecular sieve SSZ-120 (in which some or all of the structure directing agent is removed) can be used as an adsorbent or catalyst to catalyze a variety of organic compound conversion processes, including many organic compound conversion processes that are currently of commercial / industrial importance. Examples of chemical conversion processes that are effectively catalyzed by SSZ-120 itself or by a combination of SSZ-120 and one or more other catalytically active materials (including other crystalline catalysts) include those chemical conversion processes that require a catalyst with acid activity. Examples of organic conversion processes that can be catalyzed by SSZ-120 include aromatization, cracking, hydrocracking, disproportionation, alkylation, oligomerization, and isomerization.
[0070] As is the case with many catalysts, it may be desirable to blend SSZ-120 with another material that is resistant to the temperatures and other conditions used in organic conversion processes. Such materials include active and inactive materials and synthetic or naturally occurring zeolites and inorganic materials such as clays, silica and / or metal oxides such as alumina. The latter may be naturally occurring or in the form of a gelatinous precipitate or gel (including a mixture of silica and metal oxides). The use of materials in combination with active SSZ-120 (i.e., in combination with it or present in the synthesis of new materials) tends to change the conversion rate and / or selectivity of the catalyst in certain organic conversion processes. Inactive materials appropriately act as diluents to control the amount of conversion in a given process, so that products can be obtained in an economical and orderly manner without the need to employ other means for controlling the reaction rate. These materials can be incorporated into naturally occurring clays (e.g., bentonite and kaolin) to increase the compressive strength of the catalyst under commercial operating conditions. These materials (i.e., clays, oxides, etc.) act as binders for the catalyst. It is desirable to provide a catalyst with good compressive strength because it is desirable to prevent the catalyst from breaking into a powdered material in commercial applications. These clay and / or oxide binders are generally employed solely for the purpose of increasing the compressive strength of the catalyst.
[0071] Naturally occurring clays that can be compounded with SSZ-120 include montmorillonite and the kaolin family, which includes subbentonites, as well as kaolins commonly known as Dixie, McNamee, Georgia, and Florida clays, or other clays in which the major mineral components are halloysite, kaolinite, dickite, perlite, or bauxite. Such clays can be used in the original state as originally mined or in a state that has initially undergone calcination, acid treatment, or chemical modification. Binders that can be used to compound with SSZ-120 also include inorganic oxides such as silica, zirconium oxide, titanium oxide, magnesium oxide, beryllium oxide, aluminum oxide, and mixtures thereof.
[0072] In addition to the above materials, SSZ-120 can also be compounded with porous matrix materials such as silica-alumina, silica-magnesia, silica-zirconia, silica-thoria, silica-beryllia, silica-titania, and ternary compositions such as silica-alumina-thoria, silica-alumina-zirconia, silica-alumina-magnesia and silica-magnesia-zirconia.
[0073] The relative proportions of SSZ-120 and the inorganic oxide matrix can vary widely, with the SSZ-120 content ranging from 1 wt % to 90 wt % (eg, 2 wt % to 80 wt %) of the composite.
[0074] Example
[0075] The following illustrative examples are intended to be non-limiting.
[0076] Example 1
[0077] Synthesis of 3,3'-[2,6-naphthalenebis(methylene)]bis[1,2-dimethyl-1H-imidazolium] dihydroxide
[0078] A 250 mL round bottom flask equipped with a magnetic stir bar was charged with 5 g of 2,6-bis(bromomethyl)naphthalene, 3.83 g of 1,2-dimethylimidazole and 100 mL of methanol. A reflux condenser was then connected and the mixture was heated at 65 °C for 3 days. After cooling, the methanol was removed on a rotary evaporator to provide a white solid. The solid initially recovered from the rotary evaporation was further purified by recrystallization from cold ethanol. 1 H- and 13 C-NMR spectroscopy showed that the recrystallized dibromide salt was pure.
[0079] The dibromide salt was exchanged for the corresponding dihydroxide salt by stirring the dibromide salt in deionized water overnight with a hydroxide exchange resin. The solution was filtered and the filtrate was analyzed for hydroxide concentration by titrating a small sample with a standard solution of 0.1 N HCl.
[0080] Example 2
[0081] Synthesis of SSZ-120
[0082] Into a matching 23 mL Parr reactor, 0.27 g of Tosoh HSZ-390HUA Y-zeolite (SAR=500), 0.05 g of GeO 2 and 2.5 mmol of 3,3'-[2,6-naphthalenebis(methylene)]bis[1,2-dimethyl-1H-imidazolium]dihydroxide aqueous solution. The reactor was then placed in a fume hood and the water was allowed to evaporate to remove H2 O / (SiO 2 +GeO 2 ) molar ratio reaches 7 (as determined by the total mass of the suspension). Then, 2.5 mmol of HF is added and the reactor is heated to 160°C while tumbling at 43 rpm for about 7 days. The solid product is recovered by centrifugation, washed with deionized water, and dried at 95°C.
[0083] The powder XRD of the initial synthesis product gives Figure 1 The spectrum indicated in and shows that the product is a pure form of the new phase SSZ-120. A significant reduction in crystal size is inferred from the peak broadening in the powder XRD spectrum.
[0084] Figure 2(A) to Figure 2(D) Exemplary SEM images of the as-synthesized product at various magnifications are shown.
[0085] The SiO 2 / GeO 2 The molar ratio was 8 as determined by inductively coupled plasma-atomic emission spectroscopy (ICP-AES).
[0086] Example 3
[0087] Calcination of SSZ-120
[0088] The as-synthesized molecular sieve of Example 1 was calcined in a muffle furnace under an air flow heated to 550° C. at a rate of 1° C. / min and maintained at 550° C. for 5 hours, cooled, and then analyzed by powder XRD.
[0089] The powder XRD spectrum of the calcined material is shown in Figure 3 and indicate that the material remains stable after calcination to remove the structure directing agent.
[0090] Example 4
[0091] Example 2 was repeated using Zeolyst CBV780 Y-zeolite (SAR=80) as the FAU source. Powder XRD showed the product to be SSZ-120.
[0092] Example 5
[0093] Example 2 was repeated using Zeolyst CBV760 Y-zeolite (SAR=60) as the FAU source. Powder XRD showed the product to be SSZ-120.
[0094] The product was calcined as described in Example 2. The surface area of the sample was then measured using nitrogen physisorption and the data analyzed using the t-curve method. The total surface area was determined to be 693 m 2 / g and an external surface area of 144m 2 / g. The micropore volume is 0.2666cm 3 / g.
[0095] Example 6
[0096] Example 2 was repeated using Zeolyst CBV720 Y-zeolite (SAR=30) as the FAU source. Powder XRD showed the product to be SSZ-120.
[0097] Example 7
[0098] Bronsted acidity ( Acidity
[0099] The Bronsted acidity of the molecular sieve of Example 5 in its calcined form was determined by temperature programmed desorption (TPD) of n-propylamine adapted from the description published by TJ Gricus Kofke et al. (J. Catal. 1988, 114, 34-45); TJ Gricus Kofke et al. (J. Catal. 1989, 115, 265-272) and JG Tittensor et al. (J. Catal. 1992, 138, 714-720). The sample was dried in flowing H 2 The dehydrated sample was then cooled to 120°C in flowing dry helium and kept at 120°C for 30 minutes in flowing helium saturated with n-propylamine for adsorption. The n-propylamine-saturated sample was then heated to 500°C in flowing dry helium at a rate of 10°C / min. The Brønsted acidity was determined by thermogravimetric analysis based on the relationship between weight loss and temperature and by mass spectrometry based on the effluent NH 3 The Bronsted acidity of the sample is 250 μmol / g, indicating that the aluminum sites are incorporated into the framework of the molecular sieve.
[0100] Example 8
[0101] Constraint Index Test
[0102] The Constraint Index is a test used to determine the shape-selective catalytic properties in molecular sieves. It compares the reaction rates of the cracking of n-hexane (n-C6) and its isomer 3-methylpentane (3-MP) under competitive conditions (see VJ Frillette et al., J. Catal. 1981, 67, 218-222).
[0103] The hydrogen form of the molecular sieve prepared according to Example 5 was sphericalized at 4kpsi, crushed and granulated to 20-40 mesh. A 0.6g sample of the granular material was calcined at 540°C in air for 4 hours and cooled in a dryer to ensure dryness. Then, 0.47g of the material was loaded into a 1 / 4 inch stainless steel tube with alumina powder (aludum) on both sides of the molecular sieve bed. A furnace (Applied Test Systems, Inc.) was used to heat the reaction tube. Nitrogen was introduced into the reactor tube at 9.4mL / min and at atmospheric pressure. The reactor was heated to about 700°F (371°C), and a 50 / 50 feed of n-hexane and 3-methylpentane was introduced into the reactor at a rate of 8μL / min. The feed was delivered by an ISCO pump. Direct injection into the GC began 15 minutes after the feed was introduced. The test data results after running for 15 minutes (700°F) are listed in Table 5.
[0104] Table 5 Constraint index test
[0105] n-Hexane conversion, % 64.8 3-Methylpentane conversion, % 93.3 Feed conversion, % 79.1 Constraint Index (excluding 2MP) 0.39 Constraint Index (including 2MP) 0.39
[0106] Example 9
[0107] Hydrogenation conversion of n-decane
[0108] The material from Example 5 was calcined at 595°C in air for 5 hours. After calcination, 4.5 g of 0.148 N NH 4 The OH solution was mixed with 5.5 g of deionized water for three days and then with (NH 3 ) 4 Pd(NO 3 ) 2 The solution (buffered at pH 9.5) was mixed so that 1 g of this solution was mixed with 1 g of molecular sieves to provide a 0.5 wt% Pd loading, thereby loading the material with palladium. The recovered Pd / SSZ-120 material was washed with deionized water, dried at 95°C, and then calcined at 300°C for 3 hours. The calcined Pd / SSZ-120 catalyst was then sphericalized, crushed and sieved to 20-40 mesh.
[0109] 0.5 g of Pd / SSZ-120 catalyst was loaded into the center of a 23 inch long x 1 / 4 inch outer diameter stainless steel reactor tube, with alumina powder loaded upstream of the catalyst for preheating the feed (total pressure was 1200 psig; the downward flowing hydrogen rate was 160 mL / min when measured at 1 atmosphere and 25°C; and the downward flowing liquid feed rate was 1 ml / hr). All materials were first reduced in flowing hydrogen at about 315°C for 1 hour. The products were analyzed once every 60 minutes by online capillary GC. The raw data from the GC was collected by an automatic data collection / processing system, and the hydrocarbon conversion was calculated based on the raw data. The conversion is defined as the amount of n-decane produced by the reaction to produce other products (including iso-C10). The yield is expressed as the molar percentage of products other than n-decane, and includes iso-C10 isomers as output products. The results are shown in Figure 4 The results show that the catalyst is very active and has no particular selectivity for isomerization, resulting in a large amount of cracking products of n-decane.
Claims
1. An aluminum germanium silicate molecular sieve having a powder X-ray diffraction spectrum in its calcined form comprising the peaks in the following table: wherein the relative strength is represented by the following symbols: VS = very strong, i.e. >60 to 100; S = strong, i.e. >40 to 60; M = medium, i.e. >20 to 40; and W = weak, i.e. >0 to 20; and Wherein the aluminum germanosilicate molecular sieve has a composition including the following molar relationship: Al2O3:n(SiO2+GeO2) Where n≥30.
2. The aluminum germanosilicate molecular sieve of claim 1, wherein the molecular sieve comprises crystals having a nitrogen physisorption t-curve method of at least 500 m 2 / g of total surface area, and / or a surface area of at least 100 m2 as determined by the t-curve method of nitrogen physical adsorption 2 / g range of external surface area.
3. The aluminum germanium silicate molecular sieve according to claim 2, wherein the total surface area is 500 m 2 / g to 800m 2 / g range.
4. The aluminum germanium silicate molecular sieve according to claim 2, wherein the surface area is 100 m 2 / g to 300m 2 / g range.
5. An aluminum germanium silicate molecular sieve having, in its as-synthesized form, a powder X-ray diffraction spectrum comprising the peaks in the following table: wherein the relative strength is represented by the following symbols: VS = very strong, i.e. >60 to 100; S = strong, i.e. >40 to 60; M = medium, i.e. >20 to 40; and W = weak, i.e. >0 to 20; and The aluminum germanium silicate molecular sieve has the following composition expressed in molar ratio: wherein Q comprises a 3,3'-[2,6-naphthalenebis(methylene)]bis[1,2-dimethyl-1H-imidazolium] dication.
6. The aluminum germanosilicate molecular sieve of claim 5, having a chemical composition comprising the following molar relationship: wherein Q comprises a 3,3'-[2,6-naphthalenebis(methylene)]bis[1,2-dimethyl-1H-imidazolium] dication.
7. A method for synthesizing aluminum germanium silicate molecular sieve, the method comprising: (1) Providing a reaction mixture, which comprises: (a) FAU framework type zeolite; (b) Source of germanium; (c) a structure directing agent Q comprising a 3,3′-[2,6-naphthalenebis(methylene)]bis[1,2-dimethyl-1H-imidazolium] dication; (d) a fluoride ion source; and (e) water; and (2) subjecting the reaction mixture to crystallization conditions sufficient to form crystals of the aluminum germanosilicate molecular sieve; and The reaction mixture has the following composition expressed in molar ratio: 。 8. The method of claim 7, wherein the reaction mixture has the following composition expressed in molar ratio: 。 9. The method of claim 7, wherein the FAU framework-type zeolite is zeolite Y.
10. The process of claim 7, wherein the crystallization conditions comprise heating the reaction mixture at a temperature of 100°C to 200°C under autogenous pressure for a period of 1 day to 14 days.
11. A method for converting a feedstock comprising an organic compound into a conversion product, the method comprising contacting the feedstock with a catalyst comprising the aluminum germanosilicate molecular sieve of claim 1 under organic compound conversion conditions.